Gangguan Berbicara dan Berbahasa Berdasarkan Prespektif Kajian Psikolinguistik - Rohmansyah, Aurel; Rif’i Nanda Purnama, Ahmad; Gadink, Muhammad; Fatmawati, Fatmawati (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Within the scope of linguistic studies, psycholinguistics is a study that studies human behavior, language and reason. Disorders that affect a person's language skills may be caused by several diseases. Obstacles that arise due to several diseases or disorders of nerve development can have an impact on people's ability and way of speaking. Disorders in language take various forms, one of which is autism. This article aims to provide understanding and data regarding autism language disorders and how psycholinguistics views this. The method used for this study is a qualitative description method, which is a research method that provides descriptions and explanations in the form of descriptions of data based on scientific data obtained from various scientific references/literature. Based on the literature that has been collected and then analyzed and studied, the result is that autism is a form of disorder that affects the development of nerves and a person's ability to speak, interact and use the language used in language. Psycholingistics uses archetypes in acquiring one's language. In the process of language acquisition, one finds psychological or mental characteristics or symptoms which then affect one's ability to speak. One of the mental symptoms in people with autism.